2020
DOI: 10.1186/s12866-020-1703-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of enterotoxigenic extra-intestinal Bacteroides fragilis among 13-year collection of isolates in Kuwait

Abstract: Background: Some strains of Bacteroides fragilis species are associated with diarrhea as a result of enterotoxin production (bft or fragilysin). Fragilysin is activated by C11 protease (fpn) and together with C10 protease (bfp) play a significant role in its invasiveness. The objectives of this study were to investigate the proportion of clinical isolates from extra-intestinal sources that are toxin producers and characterize the genes mediating toxin production. Clinical isolates submitted to our reference la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…[ 15 22 ] The anaerobes isolated were all sensitive to the following antibiotics tested: amoxicillin clavulanate, clindamycin, metronidazole, piperacillin-tazobactam and meropenem. These findings are in line with those of Kings et al [ 23 ] whose test isolates (>1000 isolates) were all sensitive to metronidazole; Jamal et al [ 24 ] and Glupczynski et al . [ 25 ] The sensitivity pattern of the anaerobes isolated in this study may not be a good representation of the anaerobic antibiogram because of the small number of isolated anaerobes.…”
Section: Discussionsupporting
confidence: 91%
“…[ 15 22 ] The anaerobes isolated were all sensitive to the following antibiotics tested: amoxicillin clavulanate, clindamycin, metronidazole, piperacillin-tazobactam and meropenem. These findings are in line with those of Kings et al [ 23 ] whose test isolates (>1000 isolates) were all sensitive to metronidazole; Jamal et al [ 24 ] and Glupczynski et al . [ 25 ] The sensitivity pattern of the anaerobes isolated in this study may not be a good representation of the anaerobic antibiogram because of the small number of isolated anaerobes.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 15% of B. fragilis were resistant to meropenem. Similar results have been reported by Jamal et al and Wang et al, where they found 17% and 19% resistance, respectively [ 26 , 27 ], while Wybo et al reported slightly reduced resistance rates [ 28 ] at 10%. Contrary to this, Vishwanath et al [ 17 ] reported nearly complete absence of resistance for meropenem.…”
Section: Discussionsupporting
confidence: 88%
“… Bacteroides fragilis is a commensal bacterium that is found in the intestines of most people and that can become an opportunistic pathogen. Amounting to only about 0.1 to 0.5% of the total bacterial mass of the intestine, B. fragilis is the most frequently isolated anaerobe from clinical samples obtained from deep intra-abdominal abscesses, purulent skin infections, soft tissue infections ( 1 , 2 ), diarrhea, and colorectal cancer ( 3 ).…”
Section: Announcementmentioning
confidence: 99%